2012
DOI: 10.1097/iae.0b013e3182278bae
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes of Intravitreal Bevacizumab for Choroidal Neovascularization in Japanese Patients With Pathologic Myopia

Abstract: Intravitreal bevacizumab is a good treatment for eyes with nonsubfoveal CNV; however, another treatment is necessary for eyes with a subfoveally located CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 15 publications
0
38
4
Order By: Relevance
“…14,27 Previous studies that have evaluated the use of anti-VEGF therapy in myopic CNV were also rather heterogeneous, as the studies have included prior treated eyes as well as non-subfoveal CNV. [28][29][30] In order to further assess the long-term efficacy of anti-VEGF therapy for myopic CNV, we evaluated the 2-year outcomes in the use of intravitreal bevacizumab and ranibizumab as the primary treatment for subfoveal myopic CNV. We also evaluated the prognostic factors that might influence the visual outcomes following anti-VEGF therapy for myopic CNV.…”
Section: Introductionmentioning
confidence: 99%
“…14,27 Previous studies that have evaluated the use of anti-VEGF therapy in myopic CNV were also rather heterogeneous, as the studies have included prior treated eyes as well as non-subfoveal CNV. [28][29][30] In order to further assess the long-term efficacy of anti-VEGF therapy for myopic CNV, we evaluated the 2-year outcomes in the use of intravitreal bevacizumab and ranibizumab as the primary treatment for subfoveal myopic CNV. We also evaluated the prognostic factors that might influence the visual outcomes following anti-VEGF therapy for myopic CNV.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10][11][12] The mean final VA in patients treated with anti-VEGF drugs reported in the literature ranges from 0.23 to 0.55 (Table 2). [6][7][8][9][10][11][12][31][32][33][34][35][36] More importantly, in studies which have compared anti-VEGF with PDT treatment for myopic CNV, patients treated with anti-VEGF generally achieved better visual outcomes compared with the group treated with PDT. 7,24,25 It is important to note, however, that in these studies, patients…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies on treatment of myopic CNV with intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) agents have reported good clinical outcomes. [6][7][8][9][10][11][12] However, anti-VEGF agents are associated with systemic risks such as cerebrovascular accidents and other arterial thromboembolic events, especially for patients with pre-existing disease. [13][14][15][16] In addition, intravitreal injections carry the risk of infectious endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…In another prospective study, Silva et al [14] reported a significant gain of 8 letters in eyes treated with IVR. The overall sustainability of these results up to 2 years of follow-up has been documented with dichotomous outcomes; some studies revealed a loss of BCVA [18,19,20], whilst others demonstrated a maintenance of VA until 2 [21,22,23,24] and 3 years of follow-up [24] in eyes treated with IVB. Franqueira et al [25] also showed that treatment with IVR is a successful therapeutic option, improving VA for up to 3 years.…”
Section: Introductionmentioning
confidence: 99%